Optimistic Mix-net protocol based on bilinear pairings - Long-hai LI; Shao-feng FU; Rui-dan SU (Tongxin xuebao)
A novel pairing-based optimistic Mix-net scheme was proposed. The key management is made easier by em-ploying bilinear paring primitives and there is no need for the participating mix servers to re-generate keys jointly be-tween mix-sessions to avoid providing decryption oracle service to other mix-sessions. Integrity of messages during mix-ing is partially guaranteed by using dummy messages tracing technology resulting in a simpler construction for proofs“ ”of correctness. An optimization method for the joint E mal decryption involved in the protocol was also proposed, which can reduce the number of exponentiations computed by each mix server. The Mix-net will shuffle and decrypt in-put ciphertexts much faster than all previous Mix-nets with public verifiability when all mix servers execute the mixing protocol honestly.